Obstructive Sleep Apnea Treatment with Oral Appliance in a Myotonic Dystrophy Type I Subject: A Case Report - Guimarães, Maria de Lourdes Rabelo; Ribeiro, Milena Carvalho Tourino; Barbosa, Thiago Antunes da Silva; Costa, Laila Gabriela de Figueiredo; Bastos, Patricia Souza (Sleep Science, 2023)
Objective to report a myotonic dystrophy type 1 (MD1) subject with obstructive sleep apnea syndrome treated with oral appliance.Methods A review of individual's history and records, associated with a photographic register of all diagnostic methods and literature research about the topic were done.Final Statements This case depicts the therapeutical choices disposable to treat subjects with obstructive sleep apnea and DM1. Although considered an uncommon treatment, the oral appliances, if well indicated in adequately selected cases, can satisfactorily improve respiratory parameters, symptoms and quality of life.
Keywords: myotonic dystrophy type 1; sleep apnea syndromes; sleepiness; oral appliance; biomarker; therapeutics